The Pragmatic Awareness of Indonesian Nurses in Their Interactions with Foreign In-Patients - Anggoro, Sapto Dwi (Widya Mandala Surabaya Catholic University, 2016)
In hospitals, most nurses are responsible not only for caring but also building interpersonal relationships with their patients. Joint Commission International (JCI), nurses encounter foreign in-patients. This study investigated the ability of local nurses to communicate with English speaking patients in the hospital. Pragmatic awareness is the issue that becomes the focus to obtain better understanding on the nurses’ communicative aspects. It discussed how the nurses achieved successful or unsuccessful interactions in using therapeutic principles Audio recording, observations and interviews were used to see how their pragmatic awareness were applied in terms of of pragmatic principles and speech acts. The study also looked after the strategies used when unsuccessful communication with English speaking patients was solved. Some findings showed that the participants of the study could apply 11 out of 16 therapeutic communication techniques during their interactions with foreign in-patients. Meanwhile. 7 (seven) therapeutic techniques were not frequently used. In many cases the nurses avoid to apply some techniques because they were not confident their communication would be successful. A few techniques were reported to have difficulties and led to some misunderstandings. Most of the problems experienced by these nurses was triggered by languagebarrier, or their inability to formulate utterances that suited the constructions of therapeutic communication techniques. Pragmatic awareness was seen to be the major issue. It was indicated by some misunderstandings or pragmatic failure that the nurses made signalled by unexpected perlocutionary force by their foreign in-patients. Recommendations can be made in terms of language training concerning the strategies to formulate utterances in line with therapeutic communication techniques. Furthermore. nurses’ pragmatic awareness needs to be raised by improving language knowledge, especially the one dealing with pragmatic aspects. Subsequently it is recommended that the hospital allow language instructors to assist and monitor the nurses in case misunderstanding and other forms of communication problems occur. It is also important that every nurse is provided with a guide book that allows them to use it as a reference when unexpected miscommunication take place during the caring processes.